Face Perception: Domain Specific, Not Process Specific - Yovel, Galit; Kanwisher, Nancy (Neuron (Cambridge, Mass.), 2004)
Evidence that face perception is mediated by special cognitive and neural mechanisms comes from fMRI studies of the fusiform face area (FFA) and behavioral studies of the face inversion effect. Here, we used these two methods to ask whether face perception mechanisms are stimulus specific, process specific, or both. Subjects discriminated pairs of upright or inverted faces or house stimuli that differed in either the spatial distance among parts (configuration) or the shape of the parts. The FFA showed a much higher response to faces than to houses, but no preference for the configuration task over the part task. Similarly, the behavioral inversion effect was as large in the part task as the configuration task for faces, but absent in both part and configuration tasks for houses. These findings indicate that face perception mechanisms are not process specific for parts or configuration but are domain specific for face stimuli per se.